Inhibitory activity studies of the detoxifying bacterial strain “Lactobacillus brevis 121A” against Penicillium verrucosum growth and Ochratoxin A yield - Muhammad Humza; Muhammad Umar Zafar Khan; Essam Nageh Sholkamy; Abdul Basit; Babar Iqbal; Muhammad Naveed Anwar; Rida Haroon Durrani; Sanawar Ali; Francis Nosakhare Imade; Neveen Abdel-Raouf; Reem M. Alharbi; Khawla I. Alsamhary; et al. (Journal of Taibah University for Science)
This research was focused to isolate and identify antagonistic bacteria from grapes against Penicillium verrucosum growth and Ochratoxin (OTA) yield, as well as to determine the substrate and conditions that promote P. verrucosum growth and OTA yield. For this purpose, 15 culture media and 5 levels of temperature, pH and water activity were selected at which fungus was checked for growth and OTA production. Maximum growth and toxin content was observed on MEA media at temperature 25°C, pH 5.5, 0.99 water activity. Optimization and correlation show a proper link between the circumstances that promote efficient growth and OTA output (r = 0.97). Lactobacillus brevis (strain 121A) significantly retard the growth and OTA production of P. verrucosum at 108 spores/mL concentration. This strain significantly reduced grapes spoilage and increased the shelf life. This approach not only promotes biological control of fungal diseases, but also overcomes certain food safety concerns.